2021
DOI: 10.1099/mgen.0.000549
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genomic characterization of a Vibrio parahaemolyticus strain causing disease in Penaeus vannamei provides insights into its niche adaptation and pathogenic mechanism

Abstract: The virulence of Vibrio parahaemolyticus is variable depending on its virulence determinants. A V. parahaemolyticus strain, in which the virulence is governed by the pirA and pirB genes, can cause acute hepatopancreatic necrosis disease (AHPND) in shrimps. Some V. parahaemolyticus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 71 publications
5
7
0
Order By: Relevance
“…Moreover, The V. penaeicida genomes harboured the pilA , B , C and D genes encoding the components of the type IV pilus, which mediates bacterial motility on solid surfaces, host–cell adhesion, bacteriophage adsorption, microcolony formation and transformation [ 70 ]. This result is in accordance with that of a recent study, which identified a type IV pilus in the genome of V. parahaemolyticus causing disease in Penaeus vannamei [ 71 ]. QS gives bacteria the ability to control several critical processes, including virulence factor secretion, antibiotic production, biofilm formation, motility, bioluminescence, development of genetic competence and sporulation [ 72 ].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, The V. penaeicida genomes harboured the pilA , B , C and D genes encoding the components of the type IV pilus, which mediates bacterial motility on solid surfaces, host–cell adhesion, bacteriophage adsorption, microcolony formation and transformation [ 70 ]. This result is in accordance with that of a recent study, which identified a type IV pilus in the genome of V. parahaemolyticus causing disease in Penaeus vannamei [ 71 ]. QS gives bacteria the ability to control several critical processes, including virulence factor secretion, antibiotic production, biofilm formation, motility, bioluminescence, development of genetic competence and sporulation [ 72 ].…”
Section: Resultssupporting
confidence: 93%
“…This result is in accordance with that of a recent study, which identified a type IV pilus in the genome of V. parahaemolyticus causing disease in Penaeus vannamei [71]. QS gives bacteria the ability to control several critical processes, including virulence factor secretion, antibiotic production, biofilm formation, motility, bioluminescence, development of genetic competence and sporulation [72].…”
Section: Resultssupporting
confidence: 91%
“…The presence of multiple fimbriae genes associated with type I fimbriae and type IV pili indicated that EOBSR_19 was likely able to adhere to and colonize a rather wide range of hosts or environments. Similar genes are also reported earlier in other strains, including E. roggenkampii ED5 (Guo et al, 2020), E. cloacae ATCC13047 (Liu et al, 2013), Vibrio parahaemolyticus TJA114 (Zhang et al, 2021),…”
Section: Discussionsupporting
confidence: 88%
“…The habitats of aquatic invertebrates are typically characterized by bacteria and viruses. V. parahaemolyticus, a gram-negative bacterium, is a dominant autochthonous microflora found in estuarine and coastal marine environments and is linked to aquatic animal diseases (47). Interestingly, in mice, only one of the 12 TLR members, TLR4, recognizes LPS (48) whereas in shrimp, five of the nine Tolls have such a function.…”
Section: Discussionmentioning
confidence: 99%